2003
DOI: 10.1152/ajpgi.00029.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role for complement in mediating intestinal nitric oxide synthase-2 and superoxide dismutase expression

Abstract: . Role for complement in mediating intestinal nitric oxide synthase-2 and superoxide dismutase expression. Am J Physiol Gastrointest Liver Physiol 285: G197-G206, 2003. First published March 13, 2003 10.1152/ajpgi.00029.2003.-Inducible nitric oxide synthase (iNOS) and superoxide dismutase (SOD) play an important role in the pathology of ischemia-reperfusion. This study sought to determine if the proinflammatory effects of complement modulate iNOS and SOD in the rat after gastrointestinal ischemia and reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 54 publications
1
21
0
9
Order By: Relevance
“…Each gene analyzed was normalized with Gapdh, yielding a relative transcript level. Gapdh has been previously used to normalize oxidative stress related genes in different organs in the mouse (2,20,42).…”
Section: Methodsmentioning
confidence: 99%
“…Each gene analyzed was normalized with Gapdh, yielding a relative transcript level. Gapdh has been previously used to normalize oxidative stress related genes in different organs in the mouse (2,20,42).…”
Section: Methodsmentioning
confidence: 99%
“…The initial ischemic period results in cellular changes that alter subsequent signaling pathways and molecular expression (Montalto et al, 2003; Wada et al, 2001; Liangos et al, 2010). Glycolysis provides adenosine triphosphate, which during ischemia becomes depleted, and results in increased lactic acid formation and a decrease in pH.…”
Section: Ischemia-reperfusion Injuriesmentioning
confidence: 99%
“…Complement C3a and C5a have been shown to depress myocardial function in animal models [123, 124], and human studies have demonstrated strong associations between plasma concentration of C3a and postoperative myocardial dysfunction [110, 120]. Complement activation also increases the gene translation and expression of iNOS [125, 126], thus contributing to the increased NO production and vasodilation associated with vasoplegic syndrome. Additional vasoactive chemokines are released from complement‐mediated mast cell degranulation causing increased vascular permeability [114] and stimulation of the release of proteases from activated leucocytes [127].…”
Section: Inflammatory Responses To Cardiopulmonary Bypassmentioning
confidence: 99%